A KEY TO IMPROVE WORKPLACES PRODUCTIVITY - Fadillah Ismail; Nesreen Ibrahim Owaida (Jurnal Penyelidikan Sains Sosial, 2023)
Employee productivity is a significant factor influencing the performance of an organization and ensuring the success of any business. The researcher conducted a literature review of the previous study to support the objective of this research in order to gain a better understanding of the topic of effective ways to improve productivity in the workplace. The objective of the study is to determine effective ways to improve productivity in the workplace and to identify the importance of effective ways in improving the workplace’s productivity. Besides, trends of labour productivity by sectors in Malaysia have been determined in this research. In addition, this research discussed several effective ways to improve the workplace’s productivity. Meanwhile, the second subtopic explained and justified its importance. Apart from that, this research also elaborates on the ranking country with the highest labour productivity worldwide. As a result, employers and employees need to pitch in together as a whole body to improve productivity in the workplace. Last but not least, the researcher made several recommendations at the end of the study for the organization in improving its productivity.